Specific antigenic relationships between the RNA-dependent DNA polymerases of avian reticuloendotheliosis viruses and mammalian type C retroviruses. - Bauer, G (1980)
Immunoglobulin G directed against the DNA polymerase of Rauscher murine leukemia virus (R-MuLV) could bind to 125I-labeled DNA polymerase of spleen necrosis virus (SNV), a member of the reticuloendotheliosis virus (REV) species. Competition radioimmunoassays showed the specificity of this cross-reaction. The antigenic determinants common to SNV and R-MuLV DNA polymerases were shared completely by the DNA polymerases of Gross MuLV, Moloney MuLV, RD 114 virus, REV-T, and duck infectious anemia virus. Baboon endogenous virus and chicken syncytial virus competed partially for antibodies directed against the common antigenic determinants of SNV and R-MuLV DNA polymerases. DNA polymerases of avian leukosis viruses, pheasant viruses, and mammalian type B and D retroviruses and particles with RNA-dependent DNA polymerase activity from the allantoic fluid of normal chicken eggs and from the medium of a goose cell culture did not compete for the antibodies directed against the common antigenic determinants of SNV and R-MuLV DNA polymerases. We also present data about a factor in normal mammalian immunoglobulin G that specifically inhibits the DNA polymerases of REV and mammalian type C retrovirus DNA polymerases.